2022
DOI: 10.3390/plants11223183
|View full text |Cite
|
Sign up to set email alerts
|

Potassium Application Enhanced Plant Growth, Mineral Composition, Proximate and Phytochemical Content in Trachyandra divaricata Kunth (Sandkool)

Abstract: Wild leafy vegetables are commonly included in the diet of people in rural homesteads. Among various wild edible vegetables in South Africa, Trachyandra divaricata (Sandkool) is one of the most abundant but underutilized due to the dearth of literature on its cultivation and nutritional value. In the present study, the effect of potassium application and pruning on growth dynamics, mineral composition, and proximate and phytochemical content in T. divaricata were evaluated. Treatments consisted of three potass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 54 publications
1
8
0
Order By: Relevance
“…Most wild vegetables, including halophytes, have been reported to have low levels of unsaturated fats that range from 2 to 4% [21]. The amount of crude fat in the analysed samples concurs with this finding of [21] since it was lower than 3% in all tested treatments, including the control. Excessive fat in food can lead to increased cholesterol, which is a major cause of cardiovascular disorders.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Most wild vegetables, including halophytes, have been reported to have low levels of unsaturated fats that range from 2 to 4% [21]. The amount of crude fat in the analysed samples concurs with this finding of [21] since it was lower than 3% in all tested treatments, including the control. Excessive fat in food can lead to increased cholesterol, which is a major cause of cardiovascular disorders.…”
Section: Discussionsupporting
confidence: 80%
“…This improved drought tolerance under salinity may be due to osmotic adjustment through higher Na + and proline accumulation and antioxidative enzymes [64]. Nevertheless, the leaves of ice plants subjected to both salinity and water stress possessed more polyphenols and flavonols than other promising edible halophytes in South Africa, such as Chenopodium album, Trachyandra divaricata, Trachyandra ciliata [21,[65][66][67], and Tetragonia decumbens [24,68]. This suggests that the leaves of this plant may be a good source of nutritional antioxidants.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Potassium plays a major role in balancing anion uptake, movement and accumulation in plants [ 1 , 28 , 29 ]. Apoplastic concentrations may range between 2 and 26 mM K [ 2 ], cytoplasmatic K values may be between 50 to 100 mM [ 30 ], and 300 to 400 mM K concentrations may be reached in guard cells when stomata are open [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…These findings were also congruent with the findings of Shah et al [27], who discovered that increasing potassium dosages resulted in an increase in the number of leaves in Zinnia elegans. Bulawa et al [28] found that potassium doses had a favorable impact on the fresh and dry weights of T. divaricate flower buds, shoots, and roots. Furthermore, the greatest dry weight of the plant was obtained by applying 150 kg•ha −1 potassuim to the Chrysanthemum coronarium cultivar [23].…”
Section: Fertilization Effects On the Fresh And Dry Weight Of Chrysan...mentioning
confidence: 99%